Komunikasi Birokrasi Aparatur Pemerintah dalam Implementasi Undang-Undang Keterbukaan Informasi Publik (Studi Kasus Pada Dinas Komunikasi dan Informatika Provinsi Jawa Barat) - Aat Ruchiat Nugraha; Trie Damayanti (Jurnal InterAct, 2013)
Communication is an essential part of the process of information services for the public, especially the communication activities in the support of development policies implemented by the government. In relation with the development process undertaken by the government, public disclosure is often the demand of the public that information about development should be transparent, credible and accountable.  Therefore the  apparatus as part of  a  government bureaucracy  certainly have  the duty and function to serve the interests of their people through the bureaucratic form of communication. Results of the research revealed that the communication function through professional bureaucracy can convey the pattern of effective public information services and tailored to the needs of all stakeholders in the field of bureaucratic reform towards an open, honest, reliable and trustworthy.